Analisis Pemanfaatan Artificial Intelligence Dalam Membantu Proses Perekrutan Karyawan Perusahaan - Christian Iwan; Christvaldo Kurnia Putra; Dianeluoxy Zabdi; Elson Ivan Boy; Monica Agustina Chandra; Lifia Yola Febrianti (Fakultas Teknik Universitas Cenderawasih, 2023)
This article delves deep into the role of Artificial Intelligence (AI) in assisting human resources professionals in the recruitment and selection process. AI is a result of the emergence of machine learning, which can mimic human thought patterns and working mechanisms. AI, or artificial intelligence, has been applied in various fields, including quality control in manufacturing, the entertainment industry, autonomous vehicles, and is increasingly making inroads into the realm of recruitment. With the support of algorithms, AI plays a vital role in helping HR professionals filter applicant portfolios, fundamentally transforming the traditional recruitment process. Through a comprehensive analysis drawing from various literature sources, this article seeks to uncover the wide-ranging changes and profound impacts brought by AI into the world of recruitment. The conclusion drawn from this exploration is that AI has the potential to expedite the acquisition of high-quality applicants more efficiently and cost-effectively while also reducing subjectivity in human assessments. However, this transformation is not without concerns about ethics and data security, which require careful consideration.